Infrastructure and health: the salutogenic approach, interdisciplinarity and new challenges for planning and design. Issue 4 (22nd February 2022) - Patuano, Agnès; Shentova, Ralitsa; Aceska, Ana
Abstract : Purpose: The purpose of the article is to present some preliminary findings and discussions points from a symposium on Public Outdoor Spaces and COVID-19 organised in Wageningen, The Netherlands, in June 2021. Design/methodology/approach: The article argues for a salutogenic perspective on infrastructure planning and design, dealing with the interplay between the ideas and practices of infrastructure planning and design and the outcomes of those ideas and practices for health. Findings: Within that perspective, the coronavirus (COVID-19) crisis is seen as an opportunity to revive the importance of infrastructure in promoting health and well-being. Originality/value: The salutogenic approach adds a much-needed new perspective on infrastructure planning and design, and also involves challenges both in research and practice, for the application of holistic principles to the design of new environments.